POSITIVE REINFORCEMENT AND WOMEN’S PROFESSIONAL GROWTH: A STUDY ON CONFIDENCE BUILDING IN WOMEN CIRCLE NETWORK - Surya Darmadali, Waode (Journal of Islamic Culture and Literature (JICeL), 2024)
This study examines the impact of positive reinforcement on women’s confidence and linguistic development within Women Circle Networks, an initiative by Lingkar Perempuan Global in Makassar. Using Self-Determination Theory (SDT) as a framework, the research focuses on the psychological and linguistic mechanisms that drive women’s professional advancement, emphasizing autonomy, competence, and relatedness. A qualitative descriptive-analytical method was employed, with data collected through structured interviews and documentation from 20 young women aged 17 to 26. The analysis revealed that granting autonomy in language learning, such as allowing participants to choose communication scenarios aligned with their goals, significantly increased intrinsic motivation and reduced anxiety. Additionally, fostering a supportive community through mutual encouragement and constructive feedback enhanced linguistic confidence and perceived competence. The findings highlight the importance of integrating SDT principles in economic training programs to effectively empower women, recommending a balanced approach between flexibility and structured guidance. Keywords: positive reinforcement, women’s professional development, Self-Determination Theory, , Women Circle Networks